HOW DOES THE THERAPEUTIC COMMUNICATION OF MIDWIVES AFFECT THE SATISFACTION OF PREGNANT MOTHERS IN RECEIVING ANTENATAL CARE (ANC) SERVICES - Setianingsih -; Atika Kurnia Sari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Communication plays a vital role in influencing patient satisfaction, which is the primary responsibility of healthcare providers. The success of healthcare facilities and services in meeting patient expectations can increase the likelihood of patients returning to use those services, while mismatches may prompt patients to seek better facilities or feel disappointed. This study aims to assess the relationship between therapeutic communication by midwives and the satisfaction of pregnant women in antenatal care (ANC) services at Kalibalangan Public Health Center in North Lampung. The research method involves a cross-sectional approach with simultaneous measurement of independent and dependent variables in 52 randomly selected pregnant women. Statistical analysis using the Chi Square test shows significance (p) of 0.002 < 0.05 (p < α). From these results, it is concluded that therapeutic communication aims to obtain shared learning experiences to improve patients' emotional experiences. There is a significant relationship between therapeutic communication by midwives and maternal satisfaction, hence pregnant women are advised to pay attention to their pregnancy condition by attending ANC regularly and consistently visiting the Public Health Center.